Composition of essential oil and allelopathic activity of aromatic water of Aster lanceolatus Willd: (Asteraceae) - Josiane de Fátima Gaspari Dias; Obdúlio Gomes Miguel; Marilis Dallarmi Miguel (Universidade de São Paulo, 2009)
The essential oil obtained from flowers of Aster lanceolatus was submitted the CG-MS and presented as result thirteen substances with largest concentration; among them, the caryophyllene oxide with the larger one. The aromatic water obtained during the extraction process of this essential oil was forwarded to allelopathic test, and demonstrated to be capable to inhibit the germination and growth of Lactuca sativa. O óleo essencial obtido das flores de Aster lanceolatus foi submetido a CG-EM e apresentou como resultado treze substâncias, entre elas o óxido de cariofileno com a maior concentração. A água aromática obtida durante o processo de extração do óleo essencial foi encaminhada para teste alelopático, a qual demonstrou ser capaz de inibir a germinação e crescimento de Lactuca sativa.